2008
DOI: 10.1039/b717933m
|View full text |Cite
|
Sign up to set email alerts
|

A review of biosensors and biologically-inspired systems for explosives detection

Abstract: This article provides a review of the published literature describing the use of biosensors and biologically-inspired systems for explosives detection. The review focusses on the use of antibodies, enzymes, biologically-inspired synthetic ligands and whole-cell biosensors, providing a flavour of the range of technology, formats and approaches that can be used to detect explosives using biological systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
88
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(88 citation statements)
references
References 83 publications
0
88
0
Order By: Relevance
“…3 Biosensors use biological molecules usually an enzyme, antibody, or nucleic acid to detect sample molecules of interest 4 via hydrogen bonding, charge charge interactions, and other biochemical interactions. Thus the compounds require functional groups at first, a carboxy or carboxyalkyl group, so that the molecules could be linked to surfaces using amide bridges.…”
Section: Introductionmentioning
confidence: 99%
“…3 Biosensors use biological molecules usually an enzyme, antibody, or nucleic acid to detect sample molecules of interest 4 via hydrogen bonding, charge charge interactions, and other biochemical interactions. Thus the compounds require functional groups at first, a carboxy or carboxyalkyl group, so that the molecules could be linked to surfaces using amide bridges.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been known that the detection limit of bioelectronic noses depends not only on measurement technique and detecting instruments, but also on signals obtained from biological elements. [32][33][34] Thus, it can be assumed that enhancing original biological signals will improve the odorant detection of bioelectronic noses, especially olfactory cell-based biosensors. In our study, we showed the design of a nanoparticle-equipped biosensor for odorant detection.…”
Section: Discussionmentioning
confidence: 99%
“…Explosive compounds are particularly challenging to detect [7]. The target molecule of interest in the explosive 2,4,6 trinitrotoluene (TNT, molecular weight 227 g/mole).…”
Section: Commentarymentioning
confidence: 99%